Malignant peripheral nerve sheath tumour: An elusive diagnosis - Patil Karthikeya; Mahima V; Ambika L (Wolters Kluwer Medknow Publications, 2007)
Malignant peripheral nerve sheath tumour (MPNST) also termed as spindle cell malignancy of the peripheral nerve Schwann cells or neurogenic sarcoma, represents approximately 10% of all soft tissue sarcomas. This tumour is usually found in the lower extremities and only 10-12% of all lesions occur in the head and neck region, which makes it a rare entity. The diagnosis of MPNST has been described as one of the most difficult and elusive diagnosis in the soft tissue diseases because of its non-specific presentation both clinically and histopathologically. This was overcome by the use of immunohistochemistry. A case of MPNST of the left maxillary antrum in a 45 -year -old male patient is reported.